Research on Control Method for Intermediate Point Temperature of Supercritical Boiler Based on Active Disturbance Rejection Cascade Control - Junjie Gu; Xiaowei Cao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As the important signal of once-through boiler's water-fuel ratio control, intermediate point temperature of supercritical boiler plays a key role in the decision of steam and water’s boundary, the match of fuel and water, the control of main steam temperature. The condition of its control directly impacts the once-through boiler’s safety and economy running. For an uncertainty model, a good control quality can not be gained using the general PID controller when the unit load has great changes, so that the main steam temperature fluctuates greatly. According to this problem, a control system about intermediate point temperature of supercritical boiler based on active-disturbances-rejection multiple model was designed. Corresponding active disturbances rejection controller (ADRC) about different model in different operation points was designed. It can choose corresponding controller according to the operation condition so as to achieve an adaptive control of a wide range. The simulation results show that the system has a strong robustness and sufficient capability for control. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2846